Effect of Annealing on the Properties of Nanocrystalline CdS Thin Films Prepared by CBD Method - A. Djelloul; M. Adnane; Y. Larbah; M. Zerdali; C. Zegadi; A. Messaoud (Журнал нано- та електронної фізики)
The CdS thin films were deposited on glass substrate by chemical bath deposition (CBD). The effect of annealing temperature on the morphological, structural, optical and electrical properties of the crystalline CdS films were investigated for different annealing temperature (as deposited, 300, 400 and 500 °C).The annealing time is 1 h. The materials have been prepared using simple aqueous solutions containing cadmium sulfate, as source of cadmium, and thiourea as source of sulfur and ammonium hydroxide as the complexing agent. The temperature of the bath was maintained at low temperature of 80 °C. The surface morphological properties studied by SEM and AFM respectively. The structural properties of CdS thin film was studied by X-ray diffraction. The optical parameter such as transmittance and energy band gap of the films with thermal annealing temperature was investigated by UV-Visible spectrophotometer. The variation of band gap values of CdS thin film samples were found to be in the range of 2.37 to 2.5 eV. Electrical resistivity measurements were carried out in four-probe Van Der Pauw geometry at room temperature by the Hall measurement. SEM image confirmed that film of smooth surface morphology.